Antimicrobial activity of pliek u oil and pliek u crude extracts were evaluated against seven bacterial strains (Bacillus subtilis, Staphylococcus aureus, Escherichia coli, Salmonella Enteritidis, Bacillus cereus, Pseudomonas aeruginosa, Pseudomonas fluorescens) and one fungal strain (Candida albicans). Pliek u oil has been used as cooking oil and medicinal of skin diseases, wound, fever, headache and stomache. Pliek u has been consumed as spices and sambal, and also used for feed poultry. Th - Nurliana .; Mirnawati Sudarwanto; L.I. Sudirman; Anastasia Winny Sanjaya (Forum Pasca Sarjana, 2009)
Antimicrobial activity of pliek u oil and pliek u crude extracts were evaluated against seven bacterial strains (Bacillus subtilis, Staphylococcus aureus, Escherichia coli, Salmonella Enteritidis, Bacillus cereus, Pseudomonas aeruginosa, Pseudomonas fluorescens) and one fungal strain (Candida albicans).  Pliek u oil has been used as cooking oil and medicinal of skin diseases, wound, fever, headache and stomache.  Pliek u has been consumed as spices and sambal, and also used for feed poultry.  These foods collected from home industry at Redeup village in Aceh Besar, Nanggroe Aceh Darussalam.  The hexane and ethanol extracts of pliek u were obtained by standard method.  The antimicrobial activity was detected using paper disc method and the concentration of crude extract was determined by  dilution method.  Among antimicrobials extracts tested, the ethanol crude extract (EEP) was most active against all microbial strains.  The ethanol crude extract obtained from pliek u previously extracted by hexane (EERH) was active toward bacterial strains and only hexane crude extract was active against C. albicans.  The results indicated that ethanol crude extract (EEP) showed antimicrobial activity at a Minimal Inhibitory Concentration (MIC) and a Minimal Microbicidal Concentration (MMC) at 2.5-10 mg/ml and  10-20 mg/ml, respectively. EEP was still active at 100ºC, 121ºC for 15-60 minute, 28ºC (room storage), 10ºC (refrigerator temperature), both for 1-6 months and at pH from 1-11. The results of the research concluded that EEP showed significant antimicrobial activity.   Key words: pliek u, coconut fermentated, antimicrobial activity, toxicity test